Income Inequality and Chronic Health Conditions: A Multilevel Analysis of the U.S. States. Issue 1 (2nd January 2019) - Anderson, Kathryn Freeman; Bjorklund, Eric; Rambotti, Simone
ABSTRACT: Recently, scholarly work has examined the effect of rising income inequality on health outcomes. However, this work is somewhat inconclusive. The mechanisms that could produce such an association are still being sorted out. Much of this work focuses on mortality outcomes with little attention to how this process operates for actual health conditions, including chronic health problems—arguably the main public health concerns of the developed world. In a series of multilevel binary logistic regression models using data from the 2005 and 2007 Behavioral Risk Factor Surveillance System, we examine the association between state-level income inequality, poverty, and social welfare measures on spending and policy to examine the association between these factors for three chronic health outcomes: diabetes, hypertension, and coronary heart disease. We find that income inequality is conditionally positively related only to the diagnosis of diabetes and hypertension, and only in 2007. However, absolute poverty is related to the outcome across all three dependent variables. Certain social welfare measures attenuate the effects of both income inequality and absolute poverty, suggesting that some policies reduce this association.